2021
DOI: 10.1259/bjr.20201353
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical MRI study: reference values for the measurements of brainstem, cerebellar vermis, and peduncles

Abstract: Objectives: To set age-specific normal reference values for brainstem, cerebellar vermis, and peduncles measurements and characterize values’ variations according to gender, age, and age by gender interaction. Methods: 565 normal brain magnetic resonance examinations with normal anatomy and signal intensity of the supra and infratentorial structures were categorized into six age groups (infant, child, adolescent, young adult, middle-age adult, and old aged adults). Patients with congenital malformations, gross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…To assess the presence of brainstem atrophy we measured the maximal anteroposterior diameter at the level of the midbrain, midpons, and medulla on sagittal images, and compared to normative values for age according to Metwally et al 10 The corpus callosum thickness was quantified by measuring the maximum width of the body at midpoint and compared to normative values according to Gupta et al 11…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the presence of brainstem atrophy we measured the maximal anteroposterior diameter at the level of the midbrain, midpons, and medulla on sagittal images, and compared to normative values for age according to Metwally et al 10 The corpus callosum thickness was quantified by measuring the maximum width of the body at midpoint and compared to normative values according to Gupta et al 11…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the patient's age was taken into consideration by comparing the images to standard image series used in a study of a neurologically healthy population. 9 To assess the presence of brainstem atrophy we measured the maximal anteroposterior diameter at the level of the midbrain, midpons, and medulla on sagittal images, and compared to normative values for age according to Metwally et al 10 The corpus callosum thickness was quantified by measuring the maximum width of the body at midpoint and compared to normative values according to Gupta et al 11 We also reviewed and assessed the presence and characteristics of white matter abnormalities on T2-and FLAIR T2-weighted images on all planes, when available, by location (periventricular, subcortical, juxtacortical), lobar involvement (frontal, parietal, temporal, occipital, cerebellar, brainstem), and symmetry. Juxtacortical lesions were defined as lesions in direct contact with the cortical ribbon.…”
Section: Qualitative Mri Analysismentioning
confidence: 99%
“…The advent of brain imaging studies, which are now considered indispensable, made it possible to demonstrate the atrophy of the cerebellum, brainstem, spinal cord, and brain. This atrophy is even evident in presymptomatic carriers of SCA2 [2,3,13,21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Nuclear magnetic resonance (NMR) imaging is particularly useful due to its excellent tissue discrimination and its superiority over computed axial tomography by eliminating "noise" caused by bony structures in the posterior cranial fossa.…”
Section: Preliminarymentioning
confidence: 99%
“…Perhaps, with the existing low-field MRI scanners, we could have already obtained this threshold, but as of now, it remains to be determined. Reetz et al used the measurement of the maximum diameter of the midbrain as a variable, because this is one of the organs most affected by atrophy in this subtype of ataxia [3,21,[33][34][35]45]. In their study, an efficient method consisting of manual and linear delineation was proposed.…”
Section: Preliminarymentioning
confidence: 99%
“…The vestibular system projects directly to cerebellar vermis (Hitier et al, 2014). Several studies have found that cerebellar vermis is larger in men than women (Raz et al, 1992(Raz et al, , 1998(Raz et al, , 2001Tiemeier et al, 2010), although sometimes the opposite has been found (Luft et al, 1999) and some studies have found no group difference (Rhyu et al, 1999;Bernard et al, 2015;Metwally et al, 2021). Vestibular nuclei span the pons and medulla, which have been investigated in humans using diffusion tensor imaging (Bouhrara et al, 2021).…”
Section: Possible Causation Affecting the Vestibulo-collic Reflex Arcmentioning
confidence: 99%